Pengembangan Media Konseling dan Edukasi Berbahasa Banjar Berbasis Aplikasi Android pada Manajemen Posbindu PTM di Puskesmas Martapura Barat - Herman Ariadi; Akhmad Ridhoni; Akhmad Syakir (Universitas Malahayati Lampung, 2023)
ABSTRACT The Indonesian government has launched the PTM Integrated Development Post (Posbindu) program as a concrete form of controlling PTM through community empowerment activities. The role of cadres in mobilizing the community can encourage and actively participate in the community to be willing and able to participate in Posbindu PTM activities. Lack of confidence and lack of skill in Posbindu PTM cadres carrying out counseling and education at table 5, to support this, cadres need to receive information technology support that can make it easier for cadres to carry out their duties. An Android application innovation called the PEKA application (Kader Role). For cadres the PEKA application (Kader Role) is something new, to make it easier for cadres to carry out Posbindu PTM activities, especially at table 5 related to counseling and education. to develop counseling and education at the Banjar language Posbindu PTM based on an Android application. The research design uses Research and Development (RD) with the ADDIE method approach. The development method using ADDIE has 5 stages including Analyze, Design, Development, Implementation, and Evaluation. The sample in this study was 75 Posbindu PTM cadres. The test research instrument uses the Black Box Testing system and the System Usability Scale (SUS). The results of the assessment study of 75 respondents obtained a total SUS score of 6335 with an average value of 84.46 entering the EXCELLENT category with grade scale B and ACCEPTABLE acceptability range. The Cadre Role Application (PEKA) can be implemented easily and well by PTM Posbindu Cadres. Keywords: Counseling and Education Media, Cadre Role Application (PEKA), Banjarese ABSTRAK Pemerintah Indonesia telah mencanangkan program Pos Binaan Terpadu (Posbindu) PTM sebagai wujud nyata bentuk pengendalian PTM melalui kegiatan pemberdayaan masyarakat. Peran kader dalam menggerakkan masyarakat dapat mendorong dan ikut berpartisipasi aktif masyarakat untuk mau dan mampu mengikuti kegiatan Posbindu PTM. Kurang percaya diri dan kurang terampilnya kader posbindu PTM melaksanakan konseling dan edukasi di meja 5, untuk mendukung hal itu kader perlu mendapat dukungan teknologi informasi yang dapat mempermudah kader melaksanakan tugasnya. Inovasi aplikasi Android yang diberi nama aplikasi PEKA (Peran Kader). Bagi kader aplikasi PEKA (Peran Kader) ini merupakan hal baru, untuk memudahkan kader dalam pelaksanakan kegiatan posbindu PTM khususnya di meja 5 terkait dengan konseling dan edukasi. Mengembangkan konseling dan edukasi di Posbindu PTM berbahasa Banjar berbasis aplikasi Android. Desain penelitian ini menggunakan Research and Development (RD) dengan pendekatan metode ADDIE. Metode pengembangan menggunakan ADDIE memeliki 5 tahapan meliputi Analyze (Analisis), Design (Perancangan), Development (Pengembangan), Implementation (Implementasi), dan Evaluation (Evaluasi). Sampel pada penelitian berjumlahj 75 kader posbindu PTM. Instrumen penelitian pengujian menggunakan sistem Black Box Testing dan System Usability Scale (SUS). Hasil penelitian penilaian dari 75 responden diperoleh total nilai Skor SUS sebesar 6335 dengan nilai rata-rata yang dihasilkan adalah 84.46 masuk kedalam katogri EXCELLENT dengan grade scale B dan acpetability range ACCEPTABLE. Aplikasi Peran Kader (PEKA) tersebut dapat di implementasikan Kader Posbindu PTM dengan mudah dan baik. Kata Kunci: Media Konseling Dan Edukasi, Aplikasi Peran Kader (PEKA), Berbahasa Banjar